1996
DOI: 10.4319/lo.1996.41.4.0794
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance by Daphnia magna of fish and macrophytes: Chemical cues and predator‐mediated use of macrophyte habitat

Abstract: Recent biomanipulation studies suggest that macrophytes are an important refuge from fish predation for large pelagic zooplankton. We conducted two laboratory experiments that tested the behavioral responses of Daphnia magna to a macrophyte (Myriophyllum exalbescens L.) and a sunfish (Lepomis cyanellus Rafinesque) and whether responses were chemically (for fish) or structurally (for macrophytes) mediated. In the first experiment, we measured Daphnia response to four treatments in separate 38‐liter tanks. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
5
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 18 publications
6
105
5
2
Order By: Relevance
“…Lake St. Clair is now more littoral than in the 1970s, with a macrophyte cover that is approaching 100%. Such a change has been reported to have considerable effects on planktonic food webs including a reduction in phytoplankton, clearer water, and positive effects on certain groups of zooplankton (i.e., cladocerans) that use the structure as a refuge from planktivorous fishes (Schriver et al 1995, Lauridsen and Lodge 1996, van Donk and van de Bund 2002. Our observations are consistent with those reports except that the positive responses by crustacean zooplankton taxa have not occurred, suggesting resource (phytoplankton) limitation due to competition from dreissenids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lake St. Clair is now more littoral than in the 1970s, with a macrophyte cover that is approaching 100%. Such a change has been reported to have considerable effects on planktonic food webs including a reduction in phytoplankton, clearer water, and positive effects on certain groups of zooplankton (i.e., cladocerans) that use the structure as a refuge from planktivorous fishes (Schriver et al 1995, Lauridsen and Lodge 1996, van Donk and van de Bund 2002. Our observations are consistent with those reports except that the positive responses by crustacean zooplankton taxa have not occurred, suggesting resource (phytoplankton) limitation due to competition from dreissenids.…”
Section: Discussionmentioning
confidence: 99%
“…In Lake St. Clair, zebra mussels interact with zooplankton in the context of a shallow-water, high flushing rate ecosystem that has recently had a substantial increase in macrophyte distribution and biomass (Hunter and Simons 2004). An increase in macrophyte cover is reported to have substantial effects on planktonic food webs including a reduction in phytoplankton, clearer water, and positive effects on certain groups of zooplankton (i.e., cladocerans) that use the structure as a refuge from ptanktivorous fishes (Schriver et al 1995, Lauridsen and Lodge 1996, van Donk and van de Bund 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Just as macrophytes may serve as a refuge for 0ϩ roach against piscivore predation, recent studies have shown that the nonlethal presence of fish may cause Daphnia to move into the vegetation (Lauridsen and Lodge 1996); thus, macrophytes may serve as a daytime refuge for zooplankton groups performing diel migrations between vegetation and open water (Timms and Moss 1984;Lauridsen et al 1996). In our study, we observed ( As was discussed above, 0ϩ roach showed two different antipredator behaviors during the season, and we argue that both behaviors led to a lower daytime predation pressure on zooplankton in open water during the treatment periods.…”
Section: Discussionmentioning
confidence: 99%
“…In aquatic systems, some vegetation may provide such a refuge for 0ϩ fish and also for their zooplankton prey. In shallow waters, various zooplankton groups have been shown to perform diel horizontal migrations in the presence of fish-that is, they hide in the vegetation during day and use open water during night (Timms and Moss 1984;Lauridsen and Buenk 1996;Lauridsen et al 1996). This, however, means that, in the presence of a piscivorous predator, 0ϩ fish and their zooplankton prey may meet in the same refuge: zooplankton seek refuge in the presence of 0ϩ fish, and 0ϩ fish seek refuge in the presence of piscivores (Fig.…”
mentioning
confidence: 99%
“…Complexly structured macrophytes, such as submerged macrophytes, enhance the opportunities that zooplankton have for avoiding predators, and the surfaces of their stems and leaves are important attachment sites for epiphytic zooplankton (Stansfield et al, 1997;Muylaert et al, 2010), creating a complex habitat that makes a large contribution to zooplankton assemblages (Meerhoff et al, 2007). However, some reports have claimed that submerged macrophytes were mainly used by pelagic zooplankton, such as daphnids, as their daytime refuge (Lauridsen and Lodge, 1996;Burk et al, 2002), and that a large number of zooplankton species often inhabit floating-leaved or free-floating macrophytes. Moss et al (1998) and Choi et al (2014b) suggested that some epiphytic zooplankton species could attain high biomass in floating-leaved macrophyte beds.…”
Section: Taxamentioning
confidence: 99%